USING TIKTOK APPLICATION AS AN ENGLISH TEACHING MEDIA: A LITERATURE REVIEW - Fitria, Tira Nur (Universitas Lambung Mangkurat, 2023)
This study describes the use of TikTok as a teaching medium and knows its benefits on students’ English skills. This research uses library research. The analysis shows that several ways in creating learning material by using TikTok, such as downloading the TikTok app through the Play Store or AppStore, creating a text/script, recording videos, using illustrations, editing, using hashtags, and uploading into TikTok. We enter the hashtag to learn English in the search field on TikTok, then various videos will appear that match the keywords. TikTok is an innovative application that can provide students with a new sense of desire and motivation in learning English even. Several previous studies show that TikTok gives benefits to students' English skills such as speaking, listening, pronunciation, grammar, vocabulary, and pronunciation. Therefore, TikTok can be chosen as an interesting learning medium that can support the learning process. The material is simple and useful, learning is not monotonous because it is equipped with writing features that are attractive to the audio and visual when delivering material. Teachers can create a variety of materials to explain material, practices, remedial or enrichment. We also can give assignments or projects to students to make video material with TikTok an interesting, innovative, and interactive video. Students are expected to identify various types of visual elements and incorporate them into a brief video, highlighting the audio-visual form of an explanation by utilizing editing skills.